Electric vehicles and energy insecurity in ASEAN countries: Renewable energy integration and urban air quality - Chang Youngho; Yanfei Li (Asian Development Bank Institute (ADBI), 2019)
The electrification of road transport in the ASEAN appears to decrease the level of final energy consumption in the road transport sector in 2040. The level of primary energy consumption, however, may not decrease unless countries adopt aggressive policies toward the integration of renewable energy into electricity generation. This study presents the consequences of the electrification of road transport in the ASEAN in terms of various energy dimensions, namely primary and final energy consumption, the integration of renewable energy, the importing of fossil fuels, and the levels of carbon dioxide and sulfur dioxide emissions. Taking the emissions of sulfur dioxides as an indicator of the urban air quality, this study investigates whether and how the electrification of road transport helps to enhance the status of energy insecurity by improving the urban air quality. The findings of this study suggest the need to implement an aggressive fuel mix policy for electricity generation with a strong drive for electric mobility.
Keywords: N75; Q40; Q42; Q48; 330; electric mobility; urban air quality; sulfur dioxide; ASEAN; fuel mix policy for electricity generation